Analysis Of Financial Management Performance And Use Of Subsidy Funds In The Special Region Of Yogyakarta In 2021-2023 - Masithoh, Shavira Dewi; Kamela, Hurian (Utami Publisher, 2025)
Regional financial management and utilization of subsidy funds are crucial aspects in ensuring the effectiveness of development and public welfare, especially in the Special Region of Yogyakarta (DIY). This study aims to analyze the performance of financial management and the effectiveness of the use of subsidy funds in DIY in 2021–2023, by reviewing the influence of accountability, fiscal transparency, public participation, and the use of information technology. This research method uses quantitative methods. This study uses numerical and statistical data, such as the percentage of independence ratio, effectiveness, efficiency, and harmony and regional financial data such as PAD (Regional Original Income), total revenue, operating expenses, and employee expenses. Based on the analysis of the DIY regional financial ratio in 2021–2023, the level of fiscal independence remains low at 33–41%, indicating a high dependence on central funds. The effectiveness of budget use tends to be stable but not yet optimal, while the efficiency and harmony of spending are still relatively inefficient and less harmonious. The data shows an increase in PAD, but it has not been accompanied by efficient and targeted spending management. Therefore, it is necessary to improve the budget management strategy to be more independent, efficient, and in line with the needs of the community.